On the Stability of a class of Polytopes of third order square matrices and stability radius - Vázquez Silva, Efrén (2002)
In this work we investigate the stability properties of a convex symmetric timeinvariant third order matrix's polytope depending on a real positive parameter r. We apply the obtained results to the calculation of the real stability radius of a third order matrix under a certain class of affine perturbations